Work Effectiveness and Efficiency in the Perspective of Hadith: An Analysis of Islamic Education Management - Rahmah, Mutia; Sagir, Ahmad; Ansari, Adi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to study and analyze the Hadiths of the Prophet Muhammad PBUH related to the concept of work effectiveness and efficiency in the perspective of Islamic education management. The method used is library research with a thematic approach to the saheeh Hadiths contained in the pole of al-sittah. The results of the study show that Islam through the Hadiths of the Prophet Muhammad (saw) has laid a strong foundation on the importance of working effectively and efficiently. These hadiths include the principles of itqan (perfection of work), the prohibition of israf (excess), the importance of planning, professionalism, and accountability. In the context of Islamic education management, these principles can be implemented through careful planning of educational programs, optimization of educational resources, improvement of educator competence, and continuous evaluation. The findings of this research are expected to be a normative basis for managers of Islamic educational institutions in implementing effective and efficient management according to the guidance of Islamic law.